2020
DOI: 10.1002/solr.202000191
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling Contributions of Charge‐Transport Interlayers to Light‐Induced Degradation of p‐i‐n Perovskite Solar Cells

Abstract: There is growing evidence that the stability of perovskite solar cells (PSCs) is strongly dependent on the interface chemistry between the absorber films and adjacent charge‐transport layers, whereas the exact mechanistic pathways remain poorly understood. Herein, a straightforward approach is presented for decoupling the degradation effects induced by the top fullerene‐based electron transport layer (ETL) and various bottom hole‐transport layer (HTL) materials assembled in p‐i‐n PSCs. It is shown that chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…[28] The polymer PTAA may be more permeable than CuI to ion migration, such as the gradual movement of negative acceptors away from the PTAA or of positive ions into the PTAA. [29] Or, the increased vulnerability to ion migration may be due to a difference in the perovskite material itself because of its dependence on grain-size distribution [30] and crystalline quality, which can be affected by the underlying HTL. [31] Scanning electron microscope (SEM) images are shown in Figure 2, illustrating that the choice of PTAA for the HTL does change the crystallization process, resulting in rougher grains, although the grain size itself, on the order of 1 μm, was not significantly altered.…”
Section: Resultsmentioning
confidence: 99%
“…[28] The polymer PTAA may be more permeable than CuI to ion migration, such as the gradual movement of negative acceptors away from the PTAA or of positive ions into the PTAA. [29] Or, the increased vulnerability to ion migration may be due to a difference in the perovskite material itself because of its dependence on grain-size distribution [30] and crystalline quality, which can be affected by the underlying HTL. [31] Scanning electron microscope (SEM) images are shown in Figure 2, illustrating that the choice of PTAA for the HTL does change the crystallization process, resulting in rougher grains, although the grain size itself, on the order of 1 μm, was not significantly altered.…”
Section: Resultsmentioning
confidence: 99%
“…One possible pathway for such degradation is the HTM’s interactions with the perovskite decomposition products such as MAI and PbI 2 . For instance, by observing the changes in the distribution of Pb + and PbI + ions, it is found that light exposure leads to a depletion of PbI + signal near the interface between perovskite and HTM . This indicates that lead exists within the HTM in forms different from the lead iodide as it was prior to the light exposure.…”
Section: Hole Transporting Materials (Htms)mentioning
confidence: 99%
“…Du et al, prepared a NiO x /PTAA bilayer that increased the PCE up to 17.1% 43 . Moreover, PTAA bilayers were formed in conjunction with reduced graphene oxide 44 ,graphene 45 , CuO x 46 , PFN-P2 47 , NiO x 48 and VO x 49 .…”
mentioning
confidence: 99%